PENGARUH INFLASI DAN TINGKAT PENGANGGURAN TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Rani Gusri Rahayu Ningsih; Sarah Edia Putri; Radhiatul Adhawiyah; Niken Eli Marlina; Ghenia Dwi Silta; Ansofino (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of inflation and unemployment rate on economic growth in Indonesia during the 2021–2025 period. The research employs a quantitative approach using secondary data obtained from official government publications. Data were analyzed using multiple linear regression to examine the effect of each variable on economic growth. The results indicate that inflation and unemployment rate simultaneously affect economic growth in Indonesia. Partially, both inflation and unemployment rate have a negative effect on economic growth. These findings suggest that controlling inflation and reducing unemployment are essential to promote sustainable economic growth in Indonesia.